Deployment guidelines for highly congested IEEE 802.11b/g networks - Forte, A.G.; Schulzrinne, H. (2008 16th IEEE Workshop on Local and Metropolitan Area Networks, 2008)
Over the years, IEEE 802.11b/g wireless networks have been deployed in various locations such as hotels, airports and enterprises. Although IEEE 802.11b/g can be considered a mature technology, its deployment still presents challenges due to the limited number of non-overlapping channels available. This is particularly true in scenarios with a high density of users where a large number of APs covering roughly the same area is required. Through measurements we investigate different deployment scenarios, trying to provide a set of guidelines for the deployment of IEEE 802.11b/g networks so to minimize co-channel interference and maximize throughput. This, when the number of APs required to cover an area is larger than the number of non-overlapping channels available. In particular, we show how using partially overlapping channels causes lower retry rate and higher throughput than if deploying multiple APs on each of the non-overlapping channels.